The analysis of Convective Precipitaion and Dynamic Behavior of Mesoscale Convective Systems in Transition Months of Year - Daryush Yar ahmadi; Saeed Basati; Behroz Nasiri; Somayyeh Rafati (نشریه جغرافیا و برنامه‌ریزی, 2018)
Consequences and threats of climate hazards and opportunities such as water resources, agriculture and other economic sectors has caused Convective systems of precipitation are considered in recent years. Therefore, in this study, the dynamic conditions of mesoscale convective systems in the months warm and cold and their accumulation convective precipitation is investigated. After obtaining Geostationary satellites images, Meteosat and GOES, the most comprehensive of mesoscale convective systems without merge and split with the brightness temperature threshold of 224 K and area thresholds were determined and through the RegCM4, dynamic behavior and their accumulation convective precipitation was investigated. The results showed formation location of systems has been in southern Iraq and northern Saudi Arabia. The systems flows pattern of cold months of the year has been affected by altitudes pattern. So that positive vorticity in the region has been created on the collision of the elevation. Also the cores of dynamic quantities has been weakened after Zagros Mountains in months of December- January. Vorticity and convergence has been in April convective systems stronger and more intense than the months of December to January.